Novel Cement-Based Materials Using Seawater, Reused Construction Waste, and Alkali Agents - Yang Bai; Yajun Wang; Tao Yang; Xiaoyang Chen (Buildings)
This study aimed to develop marine alkali paste (MAP) produced using seawater (SW), recyclable particle material from paste specimens (RPPs), and alkali agents including NaOH (NH) and Na2O·3SiO2 (NS). The physicochemical properties and strength of the MAP were investigated with uniaxial compression tests (UCTs), an Energy-Dispersive Spectrometer (EDS), X-ray diffraction (XRD), and thermal-field emission scanning electron microscopy (SEM). The key information on the MAP preparation and experiments, including mix ratios, ages, curing, and sub-specimen locations, were recorded during the investigation. The results indicated that 8-day-old MAP prepared with NS reached a maximum compressive strength of 8.3 MPa, while 8-day-old NH-prepared specimens achieved up to 5.59 MPa. By 49 days, NS-prepared MAP had strengths between 5.46 MPa and 7.34 MPa, while the strength of NH-prepared MAP ranged from 3.59 MPa to 5.83 MPa. The key hydration products were Friedel’s salt (3CaO·Al2O3·CaCl2·10H2O, FS), xCaO·SiO2·nH2O (C-S-H), CaO·Al2O3·2SiO2·4H2O (C-A-S-H), and Na2O·Al2O3·zSiO2·2H2O (N-A-S-H). C-S-H was generated under the critical curing and working conditions in SW. C-A-S-H development contributed to C-S-H network compaction. N-A-S-H development helped in resistance to SO42− erosion, thereby cutting down ettringite (Ca6Al2(SO4)3(OH)12·26H2O) development. The active ion exchange between MAP and SW mainly involving SO42− and Cl− led to the significant formation of FS at the interface of C-A-S-H and xCaO·Al2O3·nH2O (C-A-H). Therefore, FS generation inhibited SO42− and Cl− corrosion in the MAP and rebounded the interface cracks of the hydration products. Consequently, FS contributed to the protection and development of C-S-H in the MAP, which ensured the suitability and applicability of the MAP in marine environments.